A COMPUTATIONAL STUDY ON WEAK INTERACTIONS IN HALOALKANE DEHALOGENASE OF MYCOBACTERIUM TUBERCULOSIS H37Rv - ROHINI K; SRIKUMAR P S (International Journal of Pharma and Bio Sciences, 2013)
Tuberculosis, an epidemic disease, affects one third of world population. The causative agent Mycobacterium tuberculosis is targeted in various approaches for the control of tuberculosis. The major factor of bacterial survival in the host depends on the proteins expressed in macrophages to overcome the host immunity. In this study, we carried out computational analysis on weak interactions to study the structural stability of the key enzyme haloalkane dehalogenase of Mycobacterium tuberculosis H37Rv (PDB code: 2O2H) expressed during phagocytosis. Cation–pi interactions are one of the critical weak interactions in protein involved in stability of protein. Our results showed that the number of interactions formed by arginine is higher than that by lysine in the cationic group, while those formed by phenylalanine and tyrosine are comparatively higher than by tryptophan in the pi group and that the cation-pi interaction may have a role in protein stability and environmental preference of Mycobacterium tuberculosis enzyme haloalkane dehalogenase.